2003
DOI: 10.1086/378205
|View full text |Cite
|
Sign up to set email alerts
|

Transmission/Disequilibrium Test Based on Haplotype Sharing for Tightly Linked Markers

Abstract: Studies using haplotypes of multiple tightly linked markers are more informative than those using a single marker. However, studies based on multimarker haplotypes have some difficulties. First, if we consider each haplotype as an allele and use the conventional single-marker transmission/disequilibrium test (TDT), then the rapid increase in the degrees of freedom with an increasing number of markers means that the statistical power of the conventional tests will be low. Second, the parental haplotypes cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 33 publications
1
119
1
Order By: Relevance
“…As it has been reported that analyses using haplotypes of multiple tightly linked markers are usually more informative than those using a single marker, 23,24 we decided to perform multimarker transmission disequilibrium tests in the TNFRSF14 and TNFRSF6B loci with 931 family trios from the IMSGC GWAS data (Supplementary Figure 1 and Supplementary Tables 1 and 2). For each locus, we tested the statistical significance of the most common haplotype among the transmitted set.…”
Section: Resultsmentioning
confidence: 99%
“…As it has been reported that analyses using haplotypes of multiple tightly linked markers are usually more informative than those using a single marker, 23,24 we decided to perform multimarker transmission disequilibrium tests in the TNFRSF14 and TNFRSF6B loci with 931 family trios from the IMSGC GWAS data (Supplementary Figure 1 and Supplementary Tables 1 and 2). For each locus, we tested the statistical significance of the most common haplotype among the transmitted set.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, genotyping error rates that are tolerable in the context of single-marker analysis can be unacceptable for analyses based on haplotypes. For example, Knapp and Becker 10 recently observed a dramatic inflation of the type I error rate of the haplotype-sharing transmission/disequilibrium test (HS-TDT) by Zhang et al 11 in the presence of genotyping error rates as small as 0.001. As haplotype analysis requires a higher standard of data integrity, it would be valuable to develop methods for the identification of probable genotyping errors that exploit the kind of data typically available.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of association studies, when the disease association of a specific allele is dependent on cis-acting interactions with other loci, the disease association may not be detected by testing a single allele unless the whole functional haplotype itself is analyzed. This has been demonstrated through both empirical studies (Drysdale et al 2000;Martin et al 2000) and simulation studies (Zhang et al 2002(Zhang et al , 2003. Computational algorithms and statistical methods are currently the preferred means, particularly for largescale haplotype determination.…”
Section: Discussionmentioning
confidence: 99%